Absence of the RING domain in MID1 results in patterning defects in the developing human brain - Frank, Sarah; Gabassi, Elisa; Käseberg, Stephan; Bertin, Marco; Zografidou, Lea; Pfeiffer, Daniela; Brennenstuhl, Heiko; Falk, Sven; Karow, Marisa; Schweiger, Susann (Life Science Alliance, 2024)
The X-linked form of Opitz BBB/G syndrome (OS) is a monogenic disorder in which symptoms are established early during embryonic development. OS is caused by pathogenic variants in the X-linked gene MID1 Disease-associated variants are distributed across the entire gene locus, except for the N-terminal really interesting new gene (RING) domain that encompasses the E3 ubiquitin ligase activity. By using genome-edited human induced pluripotent stem cell lines, we here show that absence of isoforms containing the RING domain of MID1 causes severe patterning defects in human brain organoids. We observed a prominent neurogenic deficit with a reduction in neural tissue and a concomitant increase in choroid plexus-like structures. Transcriptome analyses revealed a deregulation of patterning pathways very early on, even preceding neural induction. Notably, the observed phenotypes starkly contrast with those observed in MID1 full-knockout organoids, indicating the presence of a distinct mechanism that underlies the patterning defects. The severity and early onset of these phenotypes could potentially account for the absence of patients carrying pathogenic variants in exon 1 of the MID1 gene coding for the N-terminal RING domain.
CRIS-Team Scopus Importer:2024-02-02

Astrocytes and neurons share region-specific transcriptional signatures that confer regional identity to neuronal reprogramming - Herrero-Navarro, Alvaro; Puche-Aroca, Lorenzo; Moreno-Juan, Veronica; Sempere-Ferrandez, Alejandro; Espinosa, Ana; Susin, Rafael; Torres-Masjoan, Laia; Leyva-Diaz, Eduardo; Karow, Marisa; Figueres-Onate, Maria; Lopez-Mascaraque, Laura; Lopez-Atalaya, Jose P.; et al. (Science Advances, 2021)
Neural cell diversity is essential to endow distinct brain regions with specific functions. During development, progenitors within these regions are characterized by specific gene expression programs, contributing to the generation of diversity in postmitotic neurons and astrocytes. While the region-specific molecular diversity of neurons and astrocytes is increasingly understood, whether these cells share region-specific programs remains unknown. Here, we show that in the neocortex and thalamus, neurons and astrocytes express shared region-specific transcriptional and epigenetic signatures. These signatures not only distinguish cells across these two brain regions but are also detected across substructures within regions, such as distinct thalamic nuclei, where clonal analysis reveals the existence of common nucleus-specific progenitors for neurons and astrocytes. Consistent with their shared molecular signature, regional specificity is maintained following astrocyte-to-neuron reprogramming. A detailed understanding of these regional-specific signatures may thus inform strategies for future cell-based brain repair.
CRIS-Team Scopus Importer:2021-04-19

Cellular identity through the lens of direct lineage reprogramming - Falk, Sven; Han, Dandan; Karow, Marisa (Current Opinion in Genetics & Development, 2021)
Direct lineage reprogramming challenges our traditional view on basic aspects of cellular identity, and in particular on processes crucial for identity acquisition. This is partly because in direct lineage reprogramming but not during natural differentiation processes changing cellular identity can occur in the absence of mitosis. Only recently, technologies emerged to deconstruct the cellular and molecular processes governing the transitory states a cell passes through on the journey from its original identity to the new target cell fate. Here we discuss arising concepts on the nature of these transitory states and the challenges and decisions cells must conquer to reach their new cellular identity.
CRIS-Team Scopus Importer:2021-08-20

Human Induced Pluripotent Stem Cell-Derived Pericytes as Scalable and Editable Source to Study Direct Lineage Reprogramming Into Induced Neurons - Menon, Radhika; Petrucci, Linda; Lohrer, Benjamin; Zhang, Jingzhong; Schulze, Markus; Schichor, Christian; Winner, Beate; Winkler, Jürgen; Riemenschneider, Markus J.; Kühn, Ralf; Falk, Sven; Karow, Marisa (Cellular Reprogramming, 2023)
Studying human somatic cell-to-neuron conversion using primary brain-derived cells as starting cell source is hampered by limitations and variations in human biopsy material. Thus, delineating the molecular variables that allow changing the identity of somatic cells, permit adoption of neuronal phenotypes, and foster maturation of induced neurons (iNs) is challenging. Based on our previous results that pericytes derived from the adult human cerebral cortex can be directly converted into iNs (Karow et al., 2018; Karow et al., 2012), we here introduce human induced pluripotent stem cell (hiPSC)-derived pericytes (hiPSC-pericytes) as a versatile and more uniform tool to study the pericyte-to-neuron conversion process. This strategy enables us to derive scalable cell numbers and allows for engineering of the starting cell population such as introducing reporter tools before differentiation into hiPSC-pericytes and subsequent iN conversion. Harvesting the potential of this approach, we established hiPSC-derived human-human neuronal cocultures that not only allow for independent manipulation of each coculture partner but also resulted in morphologically more mature iNs. In summary, we exploit hiPSC-based methods to facilitate the analysis of human somatic cell-to-neuron conversion.
CRIS-Team Scopus Importer:2023-11-03
Keywords: direct lineage reprogramming; induced neurons; organoids; pericytes

Programming of neural progenitors of the adult subependymal zone towards a glutamatergic neuron lineage by neurogenin 2 - Péron, Sophie; Miyakoshi, Leo M.; Brill, Monika S.; Manzano-Franco, Diana; Serrano-López, Julia; Fan, Wenqiang; Marichal, Nicolás; Ghanem, Alexander; Conzelmann, Karl Klaus; Karow, Marisa; Ortega, Felipe; Gascón, Sergio; et al. (Stem Cell Reports, 2023)
Although adult subependymal zone (SEZ) neural stem cells mostly generate GABAergic interneurons, a small progenitor population expresses the proneural gene Neurog2 and produces glutamatergic neurons. Here, we determined whether Neurog2 could respecify SEZ neural stem cells and their progeny toward a glutamatergic fate. Retrovirus-mediated expression of Neurog2 induced the glutamatergic lineage markers TBR2 and TBR1 in cultured SEZ progenitors, which differentiated into functional glutamatergic neurons. Likewise, Neurog2-transduced SEZ progenitors acquired glutamatergic neuron hallmarks in vivo. Intriguingly, they failed to migrate toward the olfactory bulb and instead differentiated within the SEZ or the adjacent striatum, where they received connections from local neurons, as indicated by rabies virus-mediated monosynaptic tracing. In contrast, lentivirus-mediated expression of Neurog2 failed to reprogram early SEZ neurons, which maintained GABAergic identity and migrated to the olfactory bulb. Our data show that NEUROG2 can program SEZ progenitors toward a glutamatergic identity but fails to reprogram their neuronal progeny.
CRIS-Team Scopus Importer:2023-12-15
Keywords: adult neurogenesis; adult subventricular zone; fate reprogramming; neural specification; neural stem cell; neurogenin 2; olfactory bulb; proneural gene

Reprogramming astroglia into neurons with hallmarks of fast-spiking parvalbumin-positive interneurons by phospho-site-deficient Ascl1 - Marichal, Nicolás; Péron, Sophie; Beltrán Arranz, Ana; Galante, Chiara; Franco Scarante, Franciele; Wiffen, Rebecca; Schuurmans, Carol; Karow, Marisa; Gascón, Sergio; Berninger, Benedikt (Science Advances, 2024)
Cellular reprogramming of mammalian glia to an induced neuronal fate holds the potential for restoring diseased brain circuits. While the proneural factor achaete-scute complex-like 1 (Ascl1) is widely used for neuronal reprogramming, in the early postnatal mouse cortex, Ascl1 fails to induce the glia-to-neuron conversion, instead promoting the proliferation of oligodendrocyte progenitor cells (OPC). Since Ascl1 activity is posttranslationally regulated, here, we investigated the consequences of mutating six serine phospho-acceptor sites to alanine (Ascl1SA6) on lineage reprogramming in vivo. Ascl1SA6 exhibited increased neurogenic activity in the glia of the early postnatal mouse cortex, an effect enhanced by coexpression of B cell lymphoma 2 (Bcl2). Genetic fate-mapping revealed that most induced neurons originated from astrocytes, while only a few derived from OPCs. Many Ascl1SA6/Bcl2-induced neurons expressed parvalbumin and were capable of high-frequency action potential firing. Our study demonstrates the authentic conversion of astroglia into neurons featuring subclass hallmarks of cortical interneurons, advancing our scope of engineering neuronal fates in the brain.
CRIS-Team Scopus Importer:2024-11-08

The gut-brain axis in inflammatory bowel disease—current and future perspectives - Günther, Claudia; Rothhammer, Veit; Karow, Marisa; Neurath, Markus; Winner, Beate (International Journal of Molecular Sciences, 2021)
The gut–brain axis is a bidirectional communication system driven by neural, hormonal, metabolic, immunological, and microbial signals. Signaling events from the gut can modulate brain function and recent evidence suggests that the gut–brain axis may play a pivotal role in linking gastrointestinal and neurological diseases. Accordingly, accumulating evidence has suggested a link between inflammatory bowel diseases (IBDs) and neurodegenerative, as well as neuroinflammatory diseases. In this context, clinical, epidemiological and experimental data have demonstrated that IBD predisposes a person to pathologies of the central nervous system (CNS). Likewise, a number of neurological disorders are associated with changes in the intestinal environment, which are indicative for disease-mediated gut–brain inter-organ communication. Although this axis was identified more than 20 years ago, the sequence of events and underlying molecular mechanisms are poorly defined. The emergence of precision medicine has uncovered the need to take into account non-intestinal symptoms in the context of IBD that could offer the opportunity to tailor therapies to individual patients. The aim of this review is to highlight recent findings supporting the clinical and biological link between the gut and brain, as well as its clinical significance for IBD as well as neurodegeneration and neuroinflammation. Finally, we focus on novel human-specific preclinical models that will help uncover disease mechanisms to better understand and modulate the function of this complex system.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Ex vivo organ models; Gut-brain axis; IBD; MS; PD

Unlocking the potential of SY-stem cells - Furlanetto, Federica; Frank, Sarah; Karow, Marisa (Development, 2024)
The sixth SY-Stem Symposium, jointly organized by the Research Institute of Molecular Pathology and the Institute of Molecular Biotechnology took place in Vienna in March 2024. Again, aspiring new group leaders were given a stage to present their work and vision of their labs. To round up the excellent program, the scientific organizers included renowned keynote speakers. Here, we provide a summary of the talks covering topics such as early embryogenesis, nervous system development and disease, regeneration and the latest technologies.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Early embryogenesis; Organoids; Single cell technologies; Stem cells